Overlapping Climate Clubs under Transaction Costs - Emilson C.D. Silva; Chikara Yamaguchi (Center for Economic Studies and ifo Institute (CESifo), 2018)
We examine the formation of multilateral, hub-and-spoke and bilateral international R&D strategic alliances (overlapping climate clubs) to reduce CO2 emissions. R&D provision in clubs produces two types of positive externalities: a global public good (i.e., reduction of CO2 emissions) and knowledge spillovers in joint R&D agreements. The latter is a club good. It is perfectly excludable. Its (direct) benefits are enjoyed by the club members only. Trust plays a central role in the type of alliance formation, if any at all. Lack of trust generates transaction costs, which increase with the number of R&D collaborators. We utilize the perfectly-coalition-proof-Nash equilibrium (PCPNE) concept to refine the set of Nash equilibria. Multilateral and hub-and-spoke coalitional structures are PCPNE, even in large economies containing all nations in the globe, in the absence of income transfers, for different values of transaction costs. With income transfers, fully participated multilateral coalitional structures are not stable; however, the size of the stable coalition increases as the economy expands.
Keywords: C70; D60; D70; H40; H70; Q40; R50; 330; climate change; climate clubs; trust; coalition-proof equilibrium; overlapping coalitions; carbon capture and storage; hub-and-spoke; international environmental agreements